A Simplified Method for the Efficient Refolding and Purification of Recombinant Human GM-CSF - Thomson, Christy A.; Olson, Melanie; Jackson, Linda M.; Schrader, John W. (PLOS ONE, 2012)
Human granulocyte macrophage colony-stimulating factor (hGM-CSF) is a haematopoietic growth factor and proinflammatory cytokine. Recombinant hGM-CSF is important not only as a research tool but also as a biotherapeutic. However, rhGM-CSF expressed in E. coli is known to form inclusion bodies of misfolded, aggregated protein. Refolding and subsequent purification of rhGM-CSF from inclusion bodies is difficult with low yields of bioactive protein being produced. Here we describe a method for the isolation, refolding and purification of bioactive rhGM-CSF from inclusion bodies. The method is straightforward, not requiring extensive experience in protein refolding nor purification and using standard laboratory equipment.